The Role of Digital Transformation in the Development of Forensic Science - A. I. Usov; G. G. Omel’yanyuk; I. A. Lapina; E. S. Karpukhina; V. O. Kuznetsov (Теория и практика судебной экспертизы)
Digital transformation plays a significant role in the implementation of forensic activities due to significant current expansion of the body of evidence based on study of combined computer information received in the course of legal proceedings. The key areas of forensic activity digital transformation are considered. It is shown that the sizes of special knowledge must obligatory cover a competent understanding of modern information technologies, their functionality and development dynamics as well as their effective use feasibility in forensic activities. The combination of systematic and integrated approaches representing various aspects of expert examination makes it possible to fully implement the principles of its objectivity, comprehensiveness and completeness as key principles of forensic activities. The need in setting up and implementation of strategic projects on improving forensic activities in the context of digital transformation determines the evolvement of digital transformation doctrine of forensic science as one of the theories of forensic expertology.